Traveler's Diarrhea, vision abnormalities and unsteady gait in a young woman - Mühling, Tobias; Gundling, Felix; Helmberger, Thomas; Schepp, Wolfgang (Zeitschrift für Gastroenterologie, 2017)
We report on the course of disease in a young woman, originally admitted with suspected refractory infectious tropical traveler's diarrhea. However, symptoms did not resolve upon either symptomatic or subsequent antibiotic therapy. When neurologic deterioration was observed, imaging studies revealed a dramatic series of thromboembolic events, including intracranial hemorrhage caused by extensive sinus vein thrombosis as well as thrombi of the right cardiac ventricle. Colonic mucosal biopsy samples finally led to the histologic diagnosis of ulcerative colitis. Having excluded thrombophilia or any other disease potentially related to a prothrombotic state, we interpreted the thromboembolic events as secondary to the primary manifestation of the underlying inflammatory bowel disease.The increased risk of thromboembolic complications—especially deep vein thrombosis and pulmonary embolism—in inflammatory bowel disease is well documented in the literature. However, sinus vein thrombosis and cardiac thrombi represent a remarkable dimension of this risk and a rare course of coagulopathy secondary to an acute flare of ulcerative colitis. Still, there is a lack of awareness of this risk, resulting in poor implementation of preventive measures modifying risk factors and allowing for pharmacological prophylaxis. We therefore emphasize that—in line with the 2014 German S3 Guideline—thromboprophylaxis in the setting of an acute flare of inflammatory bowel disease is mandatory and should not be restricted because of safety concerns.
Keywords: chronisch entzündliche Darmerkrankung; Colitis ulcerosa; extraintestinale Manifestation; Morbus Crohn